Effect of hatched marking length on entering position among motorcyclists during merging in expressway - Adnan, Ammar; H., Hanafi; Radin Umar, Radin Zaid; S., Samuel; Shaffiar, Norhashimah; Abdul Hamid, Abd. Malek; Ani, Mohd Hanafi (Science International, 2018)
Despite the risky behavior among motorcyclists, merging road design is known to have influence on how motorcyclists behave during merging in traffic. Merge into the expressway through the merging lane – safe entering position – is crucial in order to minimize the risk for road crashes. The objective of this study is to evaluate the effect of hatched marking length on entering position among motorcyclists during merging in expressway. Field observation study was conducted at sixteen scenario locations with different length of the hatched marking (13 - 127 meters). In total, 3200 motorcyclists were observed (200 motorcyclists at each scenario location). Each scenario location was observed from Monday to Thursday in two observation sessions (morning session during 9:00 AM – 12:00 PM, and evening session during 2:00 PM – 5:00 PM), during a good weather and normal traffic congestion. The dependent variable is the percentage of the safe entering. If a motorcyclist merge into expressway through the merging lane, he or she was scored 1, else he or she was scored 0 (merge through the hatched marking area). Result obtained shows that: (i) almost 100% of motorcyclists merged into the expressway through the safe entering position for all scenarios with the length of hatched marking below 63 meters; and (ii) a decreasing pattern of the percentage of safe entering position was observed for the scenarios with the length of hatched marking above 63 meters. Further analysis shows that there is a strong negative correlation between the percentage of the safe entering position with the length of the hatched marking with the coefficient of determination (R2) of 0.9114. Moreover, a significant regression equation was found (F (1,2) = 20.5651, p <0.0453) with the linear regression line, y = -0.7443x + 143.81, meaning that the percentage of the safe entering is decreased by 0.7443 for each meter increment of hatched marking length. The findings recommended the hatched marking design improvement for road safety. In addition, it may contribute to improving the riding education program in general, specifically, on how to merge safely during merging in traffic.